Skills for Managers of Sustainable Projects - Todorov, Maria do Carmo Assis (2013)
The current competitive scenario leads organizations to seek new strategies, processes and management models and project management had to take into account sustainability, according to Carvalho and Rabechini (2011). This requires behavior change and for this we must develop necessary skills and innovative partnerships between society and academia (Leeuw, Wiek Buizer 2012). To meet this emerging need, this paper aims to identify which General skills Project Managers are more adherent sustainability and Specific objectives are: a) Indicate the powers of a sustainable leader b) compare these competencies with the competencies a project manager, c) Presenting skills for managers of sustainable projects. Methods: Through a descriptive and exploratory qualitative research was elaborated a survey of project managers of six (6) business practitioners of environmental management, companies classified in the Dow Jones (2012) and / or the ranked BenchMais (2011). Results: With the literature review was possible to identify the skills of sustainable leadership and compare them with the skills of a project manager. With the questionnaire was validated skills of a manager of sustainable projects.